KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL PENGARUHNYA TERHADAP KINERJA KARYAWAN (Pada Karyawan PG Kebon Agung Malang) - Muhamad Rihal Irsyada; Hadi Sunaryo; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTThe research was conducted at PG Kebon Agung Malang, East Java. The purpose of this research is to examine and analyze the effect of intellectual quotient, emotional intelligence and spiritual intelligence on employee performance.The variables used are intellectual quotient, emotional intelligence and spiritual intelligence as independent variables,  employee performance as the dependent variable. The sample used was 88 PG employees of the Agung Malang garden in East Java using the proportional stratified random method. Data collection method used is questionnaire. The analysis used includes instrument testing, classical assumption test, normality test, linear regression multiple regression, hypothesis testing and determination coefficient test using multiple linear regression analysis with the help of SPSS 14.0 for Windows software.The results showed0that intellectual quotient, emotional intelligence, and spiritual intelligence had a significant effect on the employees performance of the Malang Kebon Agung PG in East Java.Keywords : Intellectual Quotient, Emotional Intelligence, Spiritual Intelligence and Employee Performance